Learning to Stay Present: Low-Intensity Dialectical Behavior Therapy, Emotion Regulation, and Professional Agency Among Pre-Service Teachers Working with At-Risk Youth - Shimrit Telraz Cohen; Shahar Gindi (Education Sciences, 2026)
Teacher education programs increasingly recognize emotion regulation as central to teachers’ professional functioning, particularly in settings serving at-risk youth. Yet less is known about how pre-service teachers learn to apply explicit regulation skills during practicum. This qualitative study examined reflective journals written by 47 teacher trainees who participated in an eight-week low-intensity Dialectical Behavior Therapy (LI-DBT) workshop. Reflexive thematic analysis explored emotionally demanding practicum encounters, spontaneous regulation attempts, use of DBT skills, perceived well-being, and professional insights. Findings showed an uneven pattern: participants continued to report emotional flooding and difficulty accessing skills in real time, yet many began to use mindfulness, distress tolerance, and emotion-regulation skills to pause, tolerate distress, and respond more deliberately. The study suggests that LI-DBT may help translate social-emotional learning into situated professional practice in teacher education.